2009
DOI: 10.1074/jbc.m806210200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-activated Aryl Hydrocarbon Receptor Nuclear Translocator/HIF-1β Signal Pathway Up-regulates Cyclooxygenase-2 Gene Expression Associated with Squamous Cell Carcinoma

Abstract: Hypoxia-inducible factor (HIF) accumulates when tumors grow under hypoxic conditions. The genesis of tumors, however, usually involves normoxic conditions. In this study, we were interested in examining the potential role of aryl hydrocarbon receptor nuclear translocator (ARNT)/HIF-1␤ in tumor growth under normoxic conditions, specifically when cells are treated with epidermal growth factor (EGF), which is known to affect the gene expression of tumor growth-related protein COX-2 (cyclooxygenase-2). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Under hypoxic conditions, HIF-1a/ARNT dimers activate the transcription of numerous target genes whose the promoters contain a binding motif termed the hypoxia-response element (Semenza, 2001). Our previous studies indicated that ARNT regulates the transcriptional activation of genes that do not contain ARNTbinding sites, such as COX-2, 12(S)-lipoxygenase, and p21 WAF1/CIP1 (Chang et al, 2009;Huang et al, 2010). Herein, we provided evidence to show that ARNT indeed regulates gene expression in a hypoxia response element-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under hypoxic conditions, HIF-1a/ARNT dimers activate the transcription of numerous target genes whose the promoters contain a binding motif termed the hypoxia-response element (Semenza, 2001). Our previous studies indicated that ARNT regulates the transcriptional activation of genes that do not contain ARNTbinding sites, such as COX-2, 12(S)-lipoxygenase, and p21 WAF1/CIP1 (Chang et al, 2009;Huang et al, 2010). Herein, we provided evidence to show that ARNT indeed regulates gene expression in a hypoxia response element-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Transient transfection of cells with plasmids was performed with Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions but with slight modification. The luciferase activity in cell lysate was determined as described previously (Chang et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations